Discussion on the Clinical Combined Acupuncture Therapy for Hirayama’s Disease - Li, Yujie; Wang, Weigang (Journal of Contemporary Medical Practice, 2025)
Hirayama disease (HD) is a self-limiting, benign motor neuron disorder that typically manifests during adolescence, clinically characterized by muscular weakness and atrophy affecting either a single limb or the asymmetric distal segments of the upper extremities. Currently, the etiology of HD is recognized as multifactorial and remains incompletely elucidated. Owing to its low clinical prevalence and heterogeneous manifestations, this condition is frequently susceptible to misdiagnosis and underdiagnosis in clinical settings. In Western medical practice, the diagnosis of HD is established through a comprehensive evaluation integrating clinical features, imaging findings, and neuroelectrophysiological studies, with conventional treatment primarily involving cervical collar immobilization or surgical intervention. From the perspective of traditional Chinese medicine (TCM), HD is categorized as “wei syndrome” [1]. The core therapeutic principles emphasize warming yang and unblocking meridians, activating local qi in the affected channels, regulating qi and blood circulation, and restoring the dynamic balance between yin and yang. This therapeutic strategy is designed to nourish the local meridians and musculature, thereby alleviating the associated clinical symptoms.